Exploring the students’ adversity quotient in online mathematics learning during the Covid-19 pandemic - Anggraini, Tiara Wahyu; Mahmudi, Ali (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2021)
Adversity Quotient (AQ) is a person's ability to overcome difficulties someone faces. It shows how students overcome their difficulties. This study aims to describe the students’ AQ in online mathematics learning during the Covid-19 pandemic era and see if there is an effect of the number of platforms used when learning on students' AQ. A survey method is used with 2093 respondents consisting of Senior High School, Islamic Senior High School, and Vocational High School students from 32 provinces in Indonesia. The instrument of the Adversity Response Profile (ARP) questionnaire consists of 30 statements with two questions each. However, two open-ended questions were given before proceeding to the ARP questionnaire. The ARP questionnaire was made in and distributed through Google Form. The results show that students’ AQ in online mathematics learning was Camper. This means that the respondents were sufficient in overcoming difficulties when learning mathematics online, but they were quickly satisfied with the results which led them not to develop themselves further. Furthermore, there is no effect of the number of platforms used when learning mathematics online on the students' AQ.